As narrativas das mulheres trans sobre relacionamentos no YouTube: entre a abjeção, o segredo e a gestão do estigma - Fagundes, Nagel de Oliveira (2020)
This study investigates the affectivity of trans women in their involvement with cisgender and heterosexual men. The interest in disserting about the theme arose from the need to problematize the subjective and unequal loving conditions that trans women were and are conditioned in cisnormative and transphobic social structure and construction. With YouTube as a research field, a space of participatory culture that has shown increase and adherence in the number of trans people as users and consumers of the site, it was sought to understand, from the narratives of nine trans women youtubers, how reflexivity in this space is shown in their audiovisual content about their affective-loving experiences. Anchored to the search is digital and screen ethnography, methodologies that subsidized the assimilation of the digital field in the way it shapes and produces the financing of youtubers. From then on, users can turn to the narrator, through which they materialize on the network, gain a voice and visibility. Also with their bodies' reflexive capacity, we enter cisnormative models of presence, which provide greater coherence, security and attractive potential in the field of affects. This field presents doubts that are susceptible or not publicly assumed, or corresponds to romantic possibilities, due to the stigma and abjection of their charged identities. By so on, it is observed that the body is a recurring theme in their narratives, through which they materialize on the network, gain a voice and visibility. Also with their bodies' reflexive capacity they enter into cisnormative models of existence, which provide greater coherence, security and attractive potential in the field of affects. This field tends to present significant doubts if they will or won’t be publicly assumed, or if they will have corresponded to romantic possibilities, due to the stigma and abjection that their identities carry. It was verified that the abjection, the secret and the stigma are constituents of the affective-loving involvement of female trans bodies. When they carry other social markers of the difference they distantiate more from intelligibility, turning the romantic possibilities of being assumed more scarce. The abjection is identified by treating about bodies that far than cross the barriers that regulate gender and sexuality norms, they also tresspass other normative barriers. The stigma is a common experience for all they, because transgenderity is socially structured as a gender dissenting practice, adverse to normality. Finally, the secret has proven to act as a strategy for the men with whom they are involved to continue maintaining their practices of desire in activity without dealing with penalties, such as the delegitimization of their identities, sexualities and masculinities. This strategic way of men is denounced by the trans women in this research as haveing an unique purpose of hypersexualizing them and keeping them in the field of exoticization. However, with reflexivity in their audiovisual productions, they seek to break or reduce the stigma and the abjection through denunciations by expositions from daily violence in these interactions. Also with the exhibition, they become representatives for those who were experiencing the same conflicts isolated.